Accurate weight gain perception may inhibit weight loss compared to inaccurate weight gain perception among Japanese adults. Issue 4 (21st April 2021) - Endo, Shota; Kakamu, Takeyasu; Kasuga, Hideaki; Masuishi, Yusuke; Hidaka, Tomoo; Fukushima, Tetsuhito
ABSTRACT: The study investigates the association between weight gain perception and weight change over time among Japanese adults. Data were from specific health checkups held in 2013, 2014, and 2015 by National Health Insurance in Fukushima Prefecture, Japan. We included 3677 participants who gained more than 3.0kg between 2013 and 2014. Weight gain perception was asked in 2014 using a questionnaire. The participants who perceived their weight gain of more than 3kg were categorized in the accurate group and those who did not were in the inaccurate group. Multiple linear regression models were used to assess associations between weight gain perception in 2014 and weight change between 2014 and 2015. The models were adjusted for gender, age, weight in 2014, regular physical exercise, daily physical activity, and medication. Results showed that the accurate group (β=0.217; 95% confidence interval=0.037, 0.397; P=0.018) had significantly less weight loss than those in the inaccurate group. We concluded that accurate weight gain perception was associated with an increased risk of future weight gain among Japanese adults.